Is empathy consistent across species? Exploring factors that may explain convergence/divergence - Ribeiro, Ana Luisa Emauz Leite (2017)
The aim of this study was to understand the relationship between human-directed empathy (HDE) and animal directed empathy (ADE), an under known and investigated relationship. Previous studies indicated a weak association, and there was scarce information about the factors that could explain one and the other forms of empathy as well as their convergence or divergence. Chapter 1 reviews the literature on HDE and ADE, how they develop, relate, and what factors influence them together or separately. Chapter 2 presents the study of the adaptation and validation for the Portuguese population of the Animal Empathy Scale. Chapter 3 reports an investigation in which predictors of HDE and ADE were explored in two populations (Lusophone and Anglo-Saxon), showing that the two forms of empathy are influenced by different predictors. The study also confirms the existence of a weak correlation between HDE and ADE. Chapter 4 reports an experimental study with presentation of emotional stimuli in videos, where participants showed some capacity to correctly identify the emotional valence in distinct species (humans, chimpanzees and dogs), also exhibiting an electromyographic activity congruent with the emotions exhibited in the stimuli of the target species, especially when it came to dogs and humans. Finally, Chapter 5 discusses the results, their limitations and contexts, seeking to provide clues for future studies on the one hand, and also to draw some guidelines for the practice of those who work with animals.